The effectiveness of various chelates used alone or in combination with sodium hypochlorite in the removal of calcium hydroxide from root canals - Emel Uzunoglu; Sevinc Aktemur Turker; Bahar Ozcelik (Wolters Kluwer Medknow Publications, 2015)
Aim: To evaluate the effectiveness of various chelates used alone or in combination with sodium hypochlorite (NaOCl) in the removal of calcium hydroxide (Ca(OH)2 ) from root canals. Materials and Methods: The root canals of 72 mandibular incisors were prepared up to the ProTaper F2 file. Among these, six randomly selected teeth were used as negative and positive controls, while the root canals of the remaining 66 were filled with Ca(OH)2 paste for 1 week. Then, the experimental group specimens were divided into six groups (n = 11). The access cavities were reopened and the Ca(OH)2 paste in each group was removed using the following solutions: 2.5 mL ethylenediaminetetraacetic acid (EDTA; Group 1), 2.5 mL peracetic acid (PAA; Group 2), 2.5 mL QMix (Group 3), 2.5 mL NaOCl/2.5 mL EDTA (Group 4), 2.5 mL NaOCl/2.5 mL PAA (Group 5), and 2.5 mL NaOCl/2.5 mL QMix (Group 6). Digital photographs of longitudinally split specimens were imported into image analyzer software, and the amount of residual Ca (OH) 2 was recorded as a percentage of the overall canal surface area. The results were analyzed using Kruskal-Wallis and Conover-Dunn tests. Results: The canal walls in the positive control group were completely covered with Ca(OH) 2 compared with those in the negative control group. The lowest Ca(OH)2 removal efficiency was observed for Group 4 (P < 0.001), while Group 6 showed favorable results (P < 0.05). Conclusions: QMix combined with NaOCl can remove Ca(OH)2 from root canals as effectively as 17% EDTA and 1% PAA. The type and sequence of irrigants are more important than the total irrigant volume for effective Ca(OH) 2 removal.